2020
DOI: 10.3390/ani10122274
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Percutaneous Thermal Sensing Microchips for Body Temperature Measurements in Horses Prior to, during and after Treadmill Exercise

Abstract: Accurately measuring body temperature in horses will improve the management of horses suffering from or being at risk of developing postrace exertional heat illness. PTSM has the potential for measuring body temperature accurately, safely, rapidly, and noninvasively. This study was undertaken to investigate the relation between the core body temperature and PTSM temperatures prior to, during, and immediately after exercise. The microchips were implanted into the nuchal ligament, the right splenius, gluteal, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Such assessment, following Dyson et al [ 30 ], should be useful in the everyday equine practice, where a horse performs the under-rider overground exercise with turns and circles. As the practical application of modern technologies is developing dynamically both in the field of equine thermal imaging [ 62 , 63 , 64 ] and DIP of medical images [ 31 , 33 , 36 , 37 , 38 , 39 , 40 ], each new approach can ultimately reach every horse owner.…”
Section: Discussionmentioning
confidence: 99%
“…Such assessment, following Dyson et al [ 30 ], should be useful in the everyday equine practice, where a horse performs the under-rider overground exercise with turns and circles. As the practical application of modern technologies is developing dynamically both in the field of equine thermal imaging [ 62 , 63 , 64 ] and DIP of medical images [ 31 , 33 , 36 , 37 , 38 , 39 , 40 ], each new approach can ultimately reach every horse owner.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from those studies, only one laboratory-based high-intensity exercise study, comparing exercise in four horses in a cool vs. hot environment, suggested that the tail T sk evolvement pattern seemed to follow the T c pattern (using arterial blood temperature), although a statistical correlation was not investigated ( 39 ). A recent laboratory equine exercise study using the implantation of microchips, measuring muscle temperature (defined as “outer shell temperature” in that study) which may be extrapolated to field exercise in the future ( 67 ). There was a good correlation between central venous temperature (CVT) evolvement and outer shell temperature during a short bout of exercise (8–11.5 min) until CVT reached 41°C, although the outer shell temperature was reported to lag behind CVT during the recovery phase.…”
Section: Discussionmentioning
confidence: 99%
“…A recent alternative method is the use of intra-muscular microchips embedded in different locations to continuously record muscle temperature ( Kang et al, 2020 ). Although the study was performed under laboratory conditions, this technique could eventually be employed in the field.…”
Section: Discussionmentioning
confidence: 99%